2012
DOI: 10.3314/mmj.53.199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cinnamaldehyde on Hyphal Growth of C.albicans Under Various Treatment Conditions

Abstract: This study investigated the effects of cinnamaldehyde in combatting the hyphal growth of Candida albicans under varying concentrations, treatment times, and temperatures to determine the potential benefits of applying this substance to anti-Candida foods or gargles. From the results of pretreatment with cinnamaldehyde against Candida hyphae, we found that its inhibitory activity seemed to be strengthened in parallel with prolonged pretreatment time and a rise in temperature, and that pretreatment of 2,000 µg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…However inhibition of sterol biosynthesis could also be associated with anti-Candida activity of camphene [50]. Cinnamaldehyde was also known to inhibit growth of various microorganisms by affecting membrane integrity, energy generation and extended-spectrum beta-lactamase (ESBL) protein dependant drug resistance [17]- [19]. Curcumin is known to induce apoptosis in eukaryotic cells and also reported to inhibit planktonic and biofilm growth of C. albicans [20] [51].…”
Section: Discussionmentioning
confidence: 99%
“…However inhibition of sterol biosynthesis could also be associated with anti-Candida activity of camphene [50]. Cinnamaldehyde was also known to inhibit growth of various microorganisms by affecting membrane integrity, energy generation and extended-spectrum beta-lactamase (ESBL) protein dependant drug resistance [17]- [19]. Curcumin is known to induce apoptosis in eukaryotic cells and also reported to inhibit planktonic and biofilm growth of C. albicans [20] [51].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of cinnamaldehyde on a clinical isolate of C. albicans was evaluated, according with the medium temperature and time of exposition. The results shown that at 37 °C the IC50 after 60 minutes ranged from 128 μg / mL to 320 μg / mL (Taguchi et al, 2012). Interestingly our results demonstrated that minimum inhibitory concentration of cinnamaldehyde was 40 µg / mL against clinical isolates of C. albicans.…”
Section: Discussionmentioning
confidence: 56%
“…This divergence could be explained due to different grown conditions. Taguchi et al (2012) evaluated the effect of cinnamaldehyde on Candida isolates with initial adhesion of 3 hours, therefore, higher cell density. This grown condition could have influenced the results because higher amounts of cells difficult the action of antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…has not been explained, the fact that higher temperature inhibits the formation of filaments of C. albicans caused by cinnamaldehyde action has been proposed by Taguchi et al (28). Moreover, although 40°C is suitable for the growth of microorganisms, intercellular proteins and linkages that exist between the biofilm's microorganisms may temporarily loosen during growth, consequently enhancing the effect of denture cleaning due to ultrasonic vibrations.…”
Section: Discussionmentioning
confidence: 99%